A unique capsule locus in the newly designated Actinobacillus pleuropneumoniae serovar 16 and development of a diagnostic PCR assay - Bosse,JT; Li,Y; Sárközi,R; Gottschalk,M; Angen,O; Nedbalcova,K; Rycroft,AN; Fodor,L; Langford,PR (Journal of Clinical Microbiology, 2017)
Actinobacillus pleuropneumoniae causes pleuropneumonia, an economically significant, lung disease of pigs. Recently, isolates of A. pleuropneumoniae that were serologically distinct from the previously characterized 15 serovars were described, and a proposal put forward that they comprised a new serovar 16. Here we used whole genome sequencing of the proposed serovar 16 reference strain A-85/14 to confirm presence of a unique capsular polysaccharide biosynthetic locus. For molecular diagnostics, primers were designed from the capsule locus of A-85/14 and a PCR formulated that differentiated serovar 16 isolates from all 15 known serovars, and other common respiratory pathogenic/commensal bacteria of pigs. Analysis of the capsule locus of strain A-85/14 combined with the previous serological data, show the existence of a sixteenth serovar – designated serovar 16 - of A. pleuropneumoniae.